Angles of Tilted and Length of Resonator Effect on The Efficiency of A Close-Open-Type Thermoacoustic - Rinasa Agistya Anugrah; Fajar Anggara (ROTASI, 2023)
In determining the optimal design of the thermoacoustic engine, parameters were studied: tilt angle and resonator length. The purpose of this study is to find the highest efficiency in tilt angle and resonator length for a standing wave thermoacoustic engine (SWTE). The heat transfer properties therein were detected at three tilt angles of -90°, 0° and 90°, resulting in three resonator lengths variations such as 390, 780 and 1170 mm. This study was conducted to determine the magnitude of pressure amplitude using a two-pressure transducer method of recording by data acquisition and counting with Matlab software. The results of this study show that a tilt angle of 90° has the highest efficiency and a tilt angle of 0° has the lowest efficiency. A cavity length of 390mm yielded the highest SWTE efficiency, with an efficiency of 5.5%.